Bibliometric analysis of liposarcomas treatment from 2004 to 2023 - Xiaopeng Wang; Jingjing Ye; Daoning Liu; Liang Yan; Shuquan Li; Ang Lv; Chengpeng Li; Jianhui Wu; Hui Qiu; Chunyi Hao (Journal of Cancer Research and Clinical Oncology)
Abstract Background Liposarcomas are mesenchymal malignant tumors characterized by varying degrees of adipocytic differentiation that comprises approximately 20% of soft tissue sarcomas. Despite advancements in this field, there remains a need for a comprehensive understanding of the mechanisms, diagnosis, and treatment of liposarcomas. Currently, there is a lack of bibliometric surveys on the development trajectory of liposarcomas treatment, research hotspots, and author and team collaboration. Methods In this study, we obtained publications from the Web of Science database from 2004 to 2023, with a specific focus on the treatment of liposarcomas. By utilizing bibliometric methods, the data were processed to facilitate visual analysis of various aspects, including authors, countries, institutions, cocitations, keywords, references, and gene characteristics. Results The number of publications on liposarcomas treatment has increased over the past two decades, from 39 in 2004 to 232 in 2023, with the United States of America contributing the most publications. Among the institutions, the Memorial Sloan Kettering Cancer Center had the highest volume of 87 publications. Notably, Alessandro Gronchi published 63 articles on the treatment of liposarcomas in the last 20 years. Cancers is the journal with the highest number of 57 publications. High-frequency keywords in these publications included “soft tissue sarcoma”, “liposarcoma”, “retroperitoneal sarcoma”, “surgery”, “dedifferentiated liposarcoma”, “trabectedin” and “radiotherapy”. Recent trends, identified through strong citation bursts from 2020 to 2023, include next-generation sequencing, radiotherapy, and patient-derived cell lines. High-frequency genes in the liposarcomas treatment field include TP53, MDM2, CDK4, DDIT3, and CD274. Conclusions The treatment of liposarcomas has garnered increasing attention worldwide in the last 20 years. The treatment approach has shifted from surgical resection to multidisciplinary therapy. The molecular and biological characteristics of different tumor subtypes have attracted more research attention, providing an important reference for the choice of treatment. The findings of this study contribute to providing a comprehensive understanding of liposarcomas treatment among researchers. Moreover, they offer valuable perspectives that can guide future research.